2014
DOI: 10.2217/fvl.14.89
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus: Strategies to Evade Antiviral Responses

Abstract: Summary Hepatitis C virus (HCV) causes chronic liver disease and poses a major clinical and economic burden worldwide. HCV is an RNA virus that is sensed as non-self in the infected liver by host pattern recognition receptors, triggering downstream signaling to interferons (IFNs). The type III IFNs play an important role in immunity to HCV, and human genetic variation in their gene loci is associated with differential HCV infection outcomes. HCV evades host antiviral innate immune responses to mediate a persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 142 publications
(196 reference statements)
0
31
0
3
Order By: Relevance
“…The type I IFN system presents important innate immunity to effectively block virus replication (Jones et al, 2005;Morrison et al, 2013). HCV infection has been reported to inhibit antiviral IFN responses that facilitate virus replication by promoting the HCV NS3/ 4A protease-mediated cleavage of mitochondrial antiviralsignaling protein (MAVS)/TIR-domain-containing adapterinducing interferon-b (TRIF) (Gokhale et al, 2014). In the present study, we found that a natural product celastrol could effectively inhibit HCV NS3/4A protease activity and enhance IFN-mediated antiviral gene expression through HO-1 induction (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The type I IFN system presents important innate immunity to effectively block virus replication (Jones et al, 2005;Morrison et al, 2013). HCV infection has been reported to inhibit antiviral IFN responses that facilitate virus replication by promoting the HCV NS3/ 4A protease-mediated cleavage of mitochondrial antiviralsignaling protein (MAVS)/TIR-domain-containing adapterinducing interferon-b (TRIF) (Gokhale et al, 2014). In the present study, we found that a natural product celastrol could effectively inhibit HCV NS3/4A protease activity and enhance IFN-mediated antiviral gene expression through HO-1 induction (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Though the path to the active site is not very narrow, measuring from 17.2 Å to 20.5 Å between Trp126, Gln181, and Lys314, a relatively small peptide or other viral product capable of binding at or near these side groups could easily interfere with oligo synthesis. Four of these sites (and indeed most of the positively selected sites throughout the protein) are found in superficial loops which exposes them as potential targets for viral proteases in a similar fashion to hepatitis C virus N3/4A, which cleaves the antiviral MAVS protein (Gokhale, et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Of the infectious agents identified with cancer, hepatitis C virus evades antiviral systems by modulating the function of innate immune proteins, including the signalling adaptor protein MAVS (mitochondrial antiviral-signalling protein) (Gokhale et al 2014). Research shows how PAMPS trigger signalling, and that HCV, EBV, KSHV and Papillomaviridae have mechanisms for evading the immune responses (Navratil et al 2010).…”
Section: Cancerous and Non-cancerous Infectious Agentsmentioning
confidence: 99%